The Effect of Rosa Damascene L. Hydro Alcohol Petal Extract on Kidney of Male Rats Treated with Arsenic - M Mohammadi; M Mahmoodi; S Shahidi (Armaghane Danesh Bimonthly Journal, 2017)
Abstract: Background and aim: Sodium arsenite is an environmental pollutant which its amounts in industrial cities are more than other places because of its use in chemical industry and has histopathological effects on different body organs including kidney. Rosa damascene is one of the important medicinal plants. The purpose of this study, the effect of Rosa damascene L. hydro alcohol Petal extract on kidney in male rats treated with arsenic.   Methods: In this experimental study 30 male rats with 200-250gr body weight were divided randomly into 5 groups (n=6): control, negative control (treated with arsenic) and three groups of patients were affected by arsenic with 150 mg/kg b.w ,300 mg/kg b.w and 450 mg/kg b.w Rosa damascene hydro alcohol petal extract respectively. Arsenic was affected in drinking water groups and hydro alcoholic extract of rose petals for injection was injected intraperitoneally. After the injection the blood samples were collected from heart directly and BUN and creatinine were analyzed. Also the kidney tissue samples were isolated and then fixed with formaline for thepreparation of histological sections were performed stained with H & E.  Data were analyzed using one-way of statistics ANOVA and significant level was considered of P <0.05.   Results: Our results showed that the arsenic has case kidney damage. Serum level of BUN and creatinine in the control group whowed a significant increase compared to the arsenic group (P<0.001). The situation significantly decreased on the group that treated by Rosa damascene L. hydro alcohol Petal extract extract (P<0.001).   Conclusion: This study showed  that Rosa damascene  extract has protective compounds such as antioxidants and flavonoids which can protect from oxidative stresses and  arsenic -induced kidney toxicity.   Keywords: